Beyond Prosthetic Memory: Posthumanism, Embodiment, and Caregiving Robots - DeFalco, Amelia (Age, Culture, Humanities: An Interdisciplinary Journal, 2018)
Literary and cinematic speculations about the future of care, read in tandem with the rising prominence of actual robotic caregivers, foretell a future in which human interaction is no longer an inevitable feature of care relations. This essay considers the social, cultural and ethical implications of robotic care alongside a particular speculative representation of posthuman care, the 2012 film Robot and Frank. The film demonstrates how the intimacy of human/machine care relationships can supply posthumanist insights into the illusion of human invulnerability and exceptionalism that obscure the heterogeneity of embedded and embodied subjects. Not only does the film dramatize the fundamental anxieties caregiving robots incite, it also offers provocative posthumanist critiques of human exceptionalism, conjuring haptic affects that trespass the boundaries between humans and machines.